Sero-prevalence of egg drop syndrome virus (EDS-76) of some selected layer farms in Bangladesh - Md. Sohel Rana; Md. Arefin Kallol; Mahadi Hasan; Md. A. H. Zihadi; Md. Bahanur Rahman; Marzia Rahman (Veterinary Research Notes, 2022)
Objective: Egg drop syndrome (EDS-76) is a viral disease of laying birds causing pale, soft-shelled, even shell-less eggs and is considered one of the adverse effects on egg production and quality. This study was designed to conduct a sero-survey to investigate the EDS-76 virus infection in layer birds. Materials and Methods: Regarding the complaints of lower egg production and deterioration of egg quality, a total of 226 sera samples were collected randomly from 13 flocks of 8 different com¬mercial layer farms in 4 districts: Gazipur, Tangail, Shirajagnj, and Mymensingh. The hemaggluti¬nation inhibition (HI) test determined the antibody titer against the EDS-76 virus by the HI test. Results: The overall prevalence was found to be 39.82% and ranged from 0.00% to 57.89%. Out of 13 flocks across 4 districts, only 1 flock was found to be EDS negative. The flock of S2 farm in Sirajganj district had the highest sero-positivity (57.89%), followed by T1 farm in Tangail dis¬trict (54.29%) and G1 farm in Gazipur district (52.20%). The lowest (26.67%) sero-positivity was observed in the M2 flock, and no birds were found sero-positive in the M1 layer farms in the Mymensingh district. On the basis of age, maximum (48.81%) sero-prevalence was found in those flocks which were between 25 and 40 weeks of age, followed by 35.87% at the age between 18 and 24 weeks and 32.06% at the age above 41 weeks. Conclusion: The sero-prevalence study revealed that the EDS virus is prevalent in commercial layer farms with a high percentage in Bangladesh and varies from farm to farm, region to region, and age to age. [Vet. Res. Notes 2022; 2(1.000): 11-14]